An ANALYSIS OF THE EFFECTS OF REVENUE DIVERSIFICATION, CAPITAL ADEQUACY RATIO, OPERATIONAL EFFICIENCY RATIO, AND LOAN TO DEPOSIT RATIO ON THE PROFITABILITY OF CONVENTIONAL BANKING INDUSTRI - Andriyanto, Rahmad; Pimada, Laila Masruro (Arthavidya Jurnal Ilmiah Ekonomi, 2025)
The banking industry is very important for the economy because it functions as an intermediary institution that is useful for improving people's lives. Banking institutions need profit or profitability in order to survive and always carry out its function as intermediary institutions. This study aims to examine the effect of Revenue Diversification, Capital Adequacy Ratio (CAR), Operating Expenses on Operating Income (BOPO), and Loan to Deposit Ratio (LDR) on Profitability (ROA) of the Conventional Banking Industry for the period 2014-2023. The data used is the average of all conventional banks in the form of statistical data in the industry. The analysis technique used Error Corection Model (ECM). The analysis results show that Income Diversification and LDR have a positive and significant effect either in the short term or long term. BOPO has a significant negative effect either in the short or long term. Meanwhile, CAR in the short term has no effect on ROA but in the long term has a significant negative effect on ROA.